MUSHARRAF ALAM ZOQI: AN EXISTENTIAL JOURNEY - Dr Misbah Rizvi; Dr Shabnam Niaz; Dr Zaheer Abbas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Among the Urdu novelists who have made the fabric of their novels with existential thought, the name of Musharraf Alam Zoqi is prominent. Somewhere in the veins of his characters there is existential fear. Somewhere there is a grip of existential meaninglessness. Somewhere the sense of incorporeality has taken the characters under its siege. Somewhere existential boredom seems embedded in the soul of every character. Somewhere the fear of death becomes an existential condition. At some point the character feels connected to the existential concept of freedom. The interference of others is playing a role of hell for him. Sartre said "Hell is other people".